2022
DOI: 10.1186/s12864-022-08833-w
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of RNA m6A methylation in pressure overload-induced cardiac hypertrophy

Abstract: Aim To analyze and compare the mRNA N6-methyladenosine modifications in transverse aortic constriction induced mice hearts and normal mice hearts. Materials and methods Colorimetric quantification was used to probe the changes in m6A modifications in the total RNA. The expression of m6A-related enzymes was analyzed via qRT-PCR and western blotting. RNA-seq and MeRIP-seq were performed to identify genes with differences in m6A modifications or expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Although the initial primary role identified for FTO is related to energy expenditure and adiposity, recent evidence suggests that FTO is likely involved in various cardiovascular pathologies most likely secondary to changes in m6A methylation, the primary target of FTO in the nucleus and an important contributor to cardiac biology [76,77]. With respect to myocardial remodelling, current evidence obtained from both animal and clinical studies suggests that FTO is downregulated in the failing heart (as well as hypoxic cardiomyocytes) whereas upregulating FTO levels improves contractile function [78,79]. On the other hand, inhibition of FTO has been shown to reduce cardiomyopathy associated with a four-week high-fat-diet-induced hyperlipidemia in rats [80].…”
Section: Leptin and Ftomentioning
confidence: 99%
“…Although the initial primary role identified for FTO is related to energy expenditure and adiposity, recent evidence suggests that FTO is likely involved in various cardiovascular pathologies most likely secondary to changes in m6A methylation, the primary target of FTO in the nucleus and an important contributor to cardiac biology [76,77]. With respect to myocardial remodelling, current evidence obtained from both animal and clinical studies suggests that FTO is downregulated in the failing heart (as well as hypoxic cardiomyocytes) whereas upregulating FTO levels improves contractile function [78,79]. On the other hand, inhibition of FTO has been shown to reduce cardiomyopathy associated with a four-week high-fat-diet-induced hyperlipidemia in rats [80].…”
Section: Leptin and Ftomentioning
confidence: 99%
“…Mice lacking FTO specifically in cardiomyocytes showed worsened cardiac phenotype characterized by reduced ejection fraction and increased dilatation upon transverse aortic constriction (TAC) surgery, an experimental model for pressure overload-induced cardiac hypertrophy and HF [ 64 ]. TAC surgery itself led to a decreased expression of FTO while FTO overexpression attenuated the cardiac post-TAC dysfunction [ 51 , 65 ]. FTO suppression was also associated with myocardial inflammation and dysfunction during endotoxemia in mice [ 66 ].…”
Section: Am Erasers In Cardiac Physiology and Pathophysiologymentioning
confidence: 99%
“…In another study, METTL3 showed no substantial alterations in the cardiac tissue while inducing the transverse aortic constriction in a mouse model, while the FTO and WTAP expressions were attenuated. Additionally, it was discovered that cardiac hypertrophy started to develop in the mouse model 4 weeks after the transverse aortic constriction, and that the amount of total RNA that had been modified with the m 6 a codon increased in the hypertrophic heart tissues [ 177 ].…”
Section: Epigenetics Of Gene Expression and Silencingmentioning
confidence: 99%